Influence of Profitability and Capital Structure on the Firm Value of Property Companies - Mursidah Nurfadillah (Fokus Bisnis Media Pengkajian Manajemen dan Akuntansi, 2025)
This study examines the influence of profitability and capital structure on the value of property companies listed on the Indonesia Stock Exchange. The study includes a quantitative method using panel data and purposive sampling in data collection so that 51 property companies was obtained with a total of 255 sample data in the last five years, from 2018 to 2022. The results of the study found that profitability significantly affects the value of property companies. At the same time, capital structure does not have a significant effect on the relationship to the firm value of property companies. Profitability and capital structure simultaneously have a significant effect on the value of property companies. This shows that companies with debt levels from existing capital structures are able to use them effectively to increase profit growth, thus having an impact on increasing the company's value.